A comparative study between HoLEP and bipolar TURP in the treatment of benign prostatic hyperplasia - Bhargava Reddy Kanchi V; Ershad Hussain Galeti; Gousia Begum S (National Scientific Medical Center, 2023)
Introduction: Benign Prostatic Hyperplasia (BPH) is one of the most frequent diseases in men. The laser treatment for BPH has challenged TURP due to advances in laser technology, a better understanding of tissue-laser interactions and rowing clinical experience. Objective: To evaluate the safety and efficacy of HoLEP, comparing it to Bipolar TURP. Material and methods: This was a prospective study to evaluate the outcomes in BPH patients undergoing surgery by HOLEP and Bipolar TURP done between January 2018 to December 2019. A total of 80 Patients were enrolled, 40 undergoing HoLEP and the other 40 Bipolar TURP for BPH. The procedures were performed by a single surgeon. All patients with symptomatic BPH and who were candidates for surgical treatment were included. Patients with previous prostate surgery, urethral surgery, history of prostate cancer or neurogenic bladder were excluded. Results: Baseline parameters were almost similar between both the groups in terms of age, IPSS, QOL, Q max, PVR, and gland size. Operative time and resected gland weight were more in HoLEP arm (p<0.001). Catheter time and Hospital stay were significantly low in the HoLEP group (p<0.0001). Hemoglobin drop was not significant (p=0.148). IPSS at three months was similar in both groups (p=0.608). Qmax improved significantly in both groups, with 18.87 ml/s in TURP and 17.87 ml/s in HoLEP with a p-value of 0.261. PVR and QOL were similar between the two groups (P=0.914 and P=0.781). Conclusion: Both Bipolar TURP and HoLEP were effective in relieving BOO. HoLEP has equal efficacy compared to conventional bipolar TURP, with decreased hospital stay and catheter indwelling time. The learning curve of HoLEP is steep; however, it can be overcome gradually.